Evaluating the influence of knee airbags on lower limb and whole-body injury. (2nd January 2020) - McMurry, Timothy L.; Forman, Jason L.; Shaw, Greg; Crandall, Jeff R.
Abstract: Objective: Knee airbags (KABs) have become increasingly common in the vehicle fleet. Previous studies (Weaver et al., 2013, Patel et al. 2013 ) showed indications that KABs may be protective for some lower extremity injuries and associated with increased risk for others. Since KABs have become significantly more common in recent model year vehicles, we revisited these findings using the most recent available data. Methods: We compared injury rates below the knee, from the knee to the hip, and above the hip in years 2000-2015 of the National Automotive Sampling System, Crashworthiness Data System (NASS-CDS) and the Crash Injury Research and Engineering Network (CIREN). Injury rates were compared with matched analyses and with Bayesian multiple logistic regression. Results: Both analyses showed that KAB to have an Odds Ratio of approximately 0.6 for knee to hip injuries, with the Bayesian model strongly significant and the matched model borderline insignificant. In the Bayesian model, KAB was borderline significant for a decrease in above the waist injuries, while the matched model pointed toward a protective effect but was not significant. Both models pointed toward an increased risk of below knee injuries, but neither was statistically significant. Conclusions: Knee airbags may be protective for knee to hip injuries and above waist injuries. If KABs continue to be widely implemented in the vehicle fleet, the field should continue to monitor and evaluate below knee injuries.